Determination of Transformer Oil Quality Parameters by its Color Coordinates - Kozlov V.K.; Valiullina D.M.; Kurakina O.E.; Sadykov E.M. (Problems of the Regional Energetics, 2021)
The service life of transformers and, as a consequence, of the electric power systems depends largely on the chemical composition and electrical insulating properties of the oil. In this regard, much attention is paid to the control of physical and chemical indicators and operational proper-ties of transformer oils. The aim of this work is to determine the important diagnostic parameters such as the acid number and the tangent of the dielectric loss angle of the transformer oil based on the measured coordinates of the color of the transformer oil. This goal is achieved by the study of the coordinates of the transformer oils chromaticity. For this purpose, a white light source is used, which is a LED with a pumping line of 450 nm and a maximum radiation in the region of 550-560 nm, with radiation in the range from 400 to 800 nm. Sensors 1, 2, 3 allow determining the chromaticity coordinates of the measured source R, G, B (red, green, blue), due to several receivers having spectral characteristics of sensitivity in the corresponding region of the visible spectrum. The most significant result of the work was the establishment of correla-tions between the TM chromaticity coordinatesб their acid number and the tangent of the dielec-tric loss angle of TM. The significance of the results obtained was that the acid number and the tangent of the dielectric loss angle of the transformer oil could be determined by the chromatici-ty coordinates, and hence, by the color of the oil.